A Large-Scale ENIGMA Multisite Replication Study of Brain Age in Depression - Han, Laura K.M.; Dinga, Richard; Leenings, Ramona; Hahn, Tim; Cole, James H.; Aftanas, Lyubomir; Amod, Alyssa R.; Besteher, Bianca; Colle, Romain; Corruble, Emmanuelle; Couvy-Duchesne, Baptiste; Danilenko, Konstantin; et al. (bioRxiv, 2022)
Several studies have evaluated whether depressed persons have older appearing brains than their nondepressed peers. However, the estimated neuroimaging-derived “brain age gap” has varied from study to study, likely driven by differences in training and testing sample (size), age range, and used modality/features. To validate our previously developed ENIGMA brain age model and the identified brain age gap, we aim to replicate the presence and effect size estimate previously found in the largest study in depression to date (N=2,126 controls & N=2,675 cases; +1.08 years [SE 0.22], Cohen’s d=0.14, 95% CI: 0.08-0.20), in independent cohorts that were not part of the original study. A previously trained brain age model (www.photon-ai.com/enigma_brainage) based on 77 FreeSurfer brain regions of interest was used to obtain unbiased brain age predictions in 751 controls and 766 persons with depression (18-75 years) from 13 new cohorts collected from 20 different scanners. Our ENIGMA MDD brain age model generalized reasonably well to controls from the new cohorts (predicted age vs. age: r = 0.73, R2=0.47, MAE=7.50 years), although the performance varied from cohort to cohort. In these new cohorts, on average, depressed persons showed a significantly higher brain age gap of +1 year (SE 0.35) (Cohen’s d□=□□.15, 95% CI: 0.05–0.25) compared with controls, highly similar to our previous finding. This study further validates our previously developed ENIGMA brain age algorithm. Importantly, we replicated the brain age gap in depression with a comparable effect size. Thus, two large-scale independent mega-analyses across in total 32 cohorts and >3,400 patients and >2,800 controls worldwide show reliable but subtle effects of brain aging in adult depression.